La escritura inspirada y la encarnación del Verbo - Izquierdo García, L.C., Antonio (Alpha Omega, 2018)
Summary: Basing his reflection on a text from Dei Filius (Conc. Vat. I), which speaks of the analogy of faith, he applies it to Scripture inspiration. The fìrst part investigates the development of number 13 of the dogmatic constitution "Dei Verbum" (Conc. Vat. Il). The second part follows the essential threads of thought regarding the analogy througlwut history, favouring the Church Fathers, until the post-Val. Il period. Keywords: Inspiration, Incarnation, Word of God, human word Parole chiave: Ispirazione, Incarnazione, Parola di Dio, parola umana